2017
DOI: 10.1021/acs.energyfuels.7b00104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Loading in NiMo/Al2O3 Catalysts on Maya Vacuum Residue Hydrocracking

Abstract: Hydrocracking catalysts with large porosity need to be developed to treat heavy oil feedstocks rich in large molecular weight components such as asphaltenes and withstand deactivation due to coke formation. In this work, catalysts were prepared by impregnation of varying NiMo loadings on a mesoporous Al2O3 support. The effect of metal loading on the hydrocracking of a vacuum residue at three temperatures (400, 425, and 450 °C) was studied in a batch microbomb reactor. Catalysts were reutilized in a second reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…It has been shown that the morphology of the meso/macroporous γ‐alumina (MGA) strongly depends on the procedures used to be synthesized. Accordingly, different approaches such as extensively used nanocasting and sol‐gel,, techniques, have been developed to synthesize MGA and improve its porous structure.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the morphology of the meso/macroporous γ‐alumina (MGA) strongly depends on the procedures used to be synthesized. Accordingly, different approaches such as extensively used nanocasting and sol‐gel,, techniques, have been developed to synthesize MGA and improve its porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among different processes introduced to synthesize MGA, sol‐gel technique can be considered as one of the most economic approaches in which cost, wastes, and time can be optimized to get to their lowest values . However, there is no unique method to accomplish sol‐gel process and to do so, different approaches have been introduced in literatures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations